Insights on the use of genetic algorithm to tessellate voronoi structures in materials science - Luana Souza Almeida; Paulo Rangel Rios (Journal of Materials Research and Technology)
The advances in manufacturing technologies have enabled the production of Voronoi structures. The main advantage of these complex designs is their lightweight and enhanced mechanical properties, such as high buckling resistance. Some applications of Voronoi structures are in reducing the weight of automotive and aerospace parts and developing biomedical implants. Metaheuristics are being used to optimize these structures while improving their mechanical properties. Hence, in this study, a systematic review is conducted to identify the trends and gaps in the use of the Genetic Algorithm to optimize two and three-dimensional Voronoi structures. The results mapped seven application domains and suggest that future research should combine manufacturability and optimization constraints, such as additive manufacturing restrictions. In addition, alternative materials (e.g., ceramics and metals) could be used to create specimens for the mechanical tests, and other approaches to finite element simulation are required to speed up the optimization process. The quantitative analysis suggests that this is an emerging topic, with few researchers in local groups cooperating to develop the field.